Persuasion of a Privately Informed Receiver - Kolotilin, Anton; Mylovanov, Tymofiy; Zapechelnyuk, Andriy; Li, Ming (Econometrica, 2017)
Kolotilin acknowledges financial support from the Australian Research Council. Zapechelnyuk acknowledges financial support from the Economic and Social Research Council (grant no. ES/N01829X/1)